Compact band pass filter with controllable bandwidth based on low radiation spur‐line defected ground structure. Issue 12 (22nd September 2016) - Zhou, Xin Yu; Zheng, Shao Yong; Chan, Wing Shing; Ho, Derek
ABSTRACT: Radiation loss is a major problem of defected ground structures (DGSs) in past decades. This paper presents a novel band pass filter (BPF) employing low radiation spur‐line DGS (S‐LDGS) resonators and a split ring resonator (SRR). This combination results in compact size and significant reduction in radiation loss. The proposed BPF achieves controllable fractional bandwidth, ranging from 36.2% to 46.5% centered at 2.6 GHz, which covers two Wi‐MAX bands. The proposal is verified with a prototype that demonstrates good agreement between simulations and measurements. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2966–2968, 2016